Meta‐Analysis of the Risk of Immune‐Related Adverse Events With Anticytotoxic T‐Lymphocyte‐Associated Antigen 4 and Antiprogrammed Death 1 Therapies. Issue 2 (10th October 2017) - Komaki, Y; Komaki, F; Yamada, A; Micic, D; Ido, A; Sakuraba, A
Abstract : We assessed the risks of immune‐related adverse events with anticytotoxic T‐lymphocyte‐associated antigen 4 (CTLA4) and antiprogrammed death 1 (PD1) therapies by meta‐analysis. Twenty‐one studies including 11, 144 patients were found. Anti‐CTLA4 therapy was associated with a significantly higher risk of overall immune‐related adverse events: diarrhea, immune‐related colitis, pruritus, and rash compared to control therapies (relative risk (RR) = 2.43, 2.10, 11.39, 3.88, 3.87, 95% confidence interval (CI) = 1.77–3.34, 1.52–2.45, 6.30–20.59, 2.37–6.37, 2.39–6.27, P < 0.001 for all outcomes). Anti‐PD1 therapy was associated with a significantly higher risk of pruritus (RR = 4.01, 95% CI = 1.97 to 8.17, P < 0.001); however, it did not increase the risks of other adverse events. Anti‐CTLA4 and anti‐PD1 therapies have distinct features of immune‐related adverse events. The results of our study would aid the surveillance and management of immune‐related adverse events in patients receiving these therapies.